Key success factors for global pharmaceutıcal companıes ın emergıng markets - Ural, Arda (My University, 2014)
Küresel ilaç ve biyoteknoloji endüstrisi 2011 yılı sonu itibariyle yaklaşık960 milyar dolar tutarında bir hacme ulaşmış ve önceki beşyıllık dönemde ortalama yıllık % 7,8 seviyesinde bir büyümesergilemiştir. Yeniilaçkeşfi, geliştirmesi ve pazarlaması üstüne kurulu iş modeliyle, ve 20 yıllık patent hakkının sağladığı korumayla bu endüstrikalıcı ve istikrarlı bir büyüme yaşamıştır. Tarihsel olarak %80 civarındabrüt kâr marjı, %40-50 aralığındafaaliyetmarjı ve sağlıklı serbest nakitakışı sayesinde ilaç endüstrisi kârlı bir endüstri olagelmiştir. Ancak endüstrinin büyümesini sağlayan bu ilaçların patent koruma sürelerininson yıllarda teker teker dolmasıyla endüstri yaklaşık 125 milyar dolar civarında bir satış kaybı yaşamış, vegüçlü bir yeni ürün hattınınolmamasından dolayı bu kaybı telaffi edememiştir. İlaç maliyetleri çoğunlukla devletler tarafından karşılandığından endüstri genellikle olumlu bir ekonomik büyüme ortamından yararlanagelmiştir. Yavaşlayanküresel ekonomive yaşlanan nüfusa bağlı artansağlıkkaynakları kullanımı, özellikleAmerika BirleşikDevletleri veAvrupaBirliğiülkelerinde sağlığa ayrılan fonların ekonomiye oranının artmasına neden olup endüstrinin aleyhinde bir durum yaratmıştır. Sonuç olarak ilaç şirketleri bu olumsuzpiyasa koşullarının üstünden gelmek vebüyümelerinisürdürmek içinyeni büyüme stratejileri arama yoluna gitmiş, vesüratlegelişmekte olan, ve Türkiye'nin de dahil kabul edildiği Yükselen BRIC(Brezilya, Hindistan, ÇinveBrezilya) Pazarlarına öncelik vermişlerdir. Bu ekonomilerin, %5-10 yıllık GSYİH büyüme sergilemeleri, nüfuslarının sağlık hizmetlerine erişiminin ve ihtiyariharcamalarının artması tümküresel ilaç şirketleriiçinumut verici birgörünümsunmuştur. Ancak, hergelişmekte olan piyasakendine özgünsosyo-ekonomik ve politik özellikler gösterdiğindengelişmiş piyasalardabaşarılı olmuş yöntemleri aynen uygulamak aynı başarıyı tekrarlamaya yeterli olmayacaktır. Bir önliteratür taramasıbuaraştırma konusununincelenmediğini ortaya koymuştur. Butezinamacı Yükselen Pazarlarda ilaç ve biyoteknoloji şirketlerininkârlı büyümesini teminen nitelvenicel olarak başarı etmenlerini araştırmaktır. Niteliksel araştırma yöntemi akademik kurumlarca basılmışyayınları, düşüncetankları, yaşam bilimlerisanayidergileri, hükümetlerveyönetim danışmanlıkfirmalarının yayınları taranması ve bahsi geçen başarılı uygulamaların saptanması şeklinde gerçekleştirilmiştir. Retrospektif gözlemselmalianalizigerçekleştirmek amacıyla ise, küresel ölçektefaaliyet gösteren en büyük 14ilaç vebiyoteknoloji şirket verileri yatırımcılara açık kaynaklardan derlenmiş, ve endüstride yaygın olarak kullanılan finansal yaklaşım yöntemi kullanılarak ikiayrı gruptaincelenmiştir. Sermayekârlılığı ve yatırımcılara geri dönüş değişkenleri 2009 den2011'i kapsayanüç yıllık birsüre içindedeğerlendirilmiştir. 2007-2011dönemine de bakılmakla beraber 2008ekonomik krizinin olumsuz ve tekil etkileri dolayısıyla bu dönemi kullanmaktan vazgeçilmiştir. Buçalışma, ilaç ve biyoteknolojişirketleri için bu firmaların ürün portföylerinin farklı olmasından dolayı, ayrı ayrı tekrarlanmıştır.Karşıılaştırmalıçıkarıma gidebilmek içintakvim ve maliyıllarnormalize edilmiştir. Araştırmaya alınan ilaç ve biyoteknoloji firmaları AmerikaBirleşik Devletleri, İngiltereveyaİsviçre merkezli, dünya çapındaoperasyonları olan,yıllık satışları 20 ila61 milyar dolar aralğında ve hisseleri NYSE veya NASDAQ’ta işlem gören firmalar arasından derlenmiştir. Yatırımcıya Geri Dönüşve Yatırılan Sermaye Dönüşü parametrelrini belirlemek için kamuya aşık şirketlerin malikaynaklarıtoplanmış vedaha sonrakarşılaştırmalısonuç eldeedebilmek içintakvim yıllarıyla firmaların maliyıllarıayarlanmak suretiylenormalize edilmiştir. Nitel çalışma ilaç ve biyoteknoloji firmalarının Gelişmekte OlanPazarlarda yatırımcıdeğeri oluşturmak ve rekabetçi kalmak için tez kapsamında bulunan yedibaşarı faktörü aşağıda sıralanmıştır: 1. Yerli Üretim Yapabilme Kabiliyeti 2. Hızlı ve iyi ilişkilere dayanan Ruhsat ve Düzenleme Yetenekleri 3. Ticari Organizasyon ModelininYükselen Pazar Koşullarınahitabedebilmesi 4. GenişveVerimli bir Dağıtım Ağına Sahib olabilmek 5. Devlet İhalelerinde Dinamik FiyatlandırmaYetenekleri 6. Yerel Klinil Çalışma yapan düşünce liderlerini küreselKlinik Çalışma ve ürün geliştirme yapan liderlerlebütünleştirebilen bir Medikal Bölüm kabiliyeti, ve 7. Yetkin ve yetenekli yerel personele erişim, işe alma ve işte tutma becerisi. Nicel olaraksa, Amerika BirleşikDevletleri’nde elde edilensatışYatırımcıya Geri Dönüş itibariylepozitif birkorelasyon gösterirken Yükselen Pazarlardakı satış geliri ilepozitif bir korelasyongörülmemiştir. Aynı örneklem için, Yatırılan Sermaye Kârlılığı hemilaç ve biyoteknolojifirmalarının satış gelirleri ilepozitif bir korelasyongöstermiştir. Bu bulgular, firmaların Yükselen Pazarlara girerken Yatırımcıya Geri Dönüş açısından getiri beklememelerini ve Yatırılan Sermaye Geri dönüşübazında da mütevazıbir beklentiiçinde olmalarını ortaya koymaktadır.

The global pharmaceutical industry generated approximately $960 billion in revenue in 2011 demonstrating a 7.8% compounded annual growth rate (CAGR) for the preceding five years. This industry, with its foundation in discovering, developing and marketing innovative medications had the benefit of patent lives -lasting around 20 years- providing sustenance for the business to grow steadily. It has been historically a profitable business with gross margins around 80% and operating margins in the range of 40-50%. While the industry enjoyed sustained free cash flow, over the last few years, it has been challenged by the expiry of patents of its products leading to massive revenue losses estimated around $125 billion and lack of a robust product pipeline to replace the lost revenue. Since the industry heavily relies on the governments to pay for its medicinal products, it thrives on a healthy economic mega-system. Industry’s challenge was further compounded by a slowing global economy and an aging population utilizing more healthcare resources and increasing healthcare costs in developed countries, particularly in the United States and the European Union countries. These unfavorable market conditions pushed the pharmaceutical companies to identify new strategic value levers to sustain its growth, and consequently the industry set out to expeditiously expand its footprint in the emerging markets. As the beneficiaries of the globalizing economy, the BRIC (Brazil, India, China & Brazil) bloc of countries and Turkey had offered the biggest growth platform. These economies have demonstrated a vivid GDP growth in the range of 5-10% annual growth and, thanks to an increase in access to medicine and surge in discretionary spending of their population; offer a promising outlook to all global companies. In this context, products of pharmaceutical companies are well-positioned to address healthcare needs of the growing and aging populations in the Emerging Markets. Nonetheless, each individual emerging market demonstrates unique socio-economic and political characteristics, and even as a bloc do not present characteristics similar to developed markets due to a variety of underlying reasons. A preliminary literature review had indicated that this research topic was not sufficiently examined leaving an opportunity to investigate. Consequently, the objective of the thesis was established to explore this non-trivial Emerging Markets growth challenge on qualitative and quantitative fronts that would link both business strategy and financial outcome aspects to the pressing dilemma of profitably growing in the Emerging Markets. In order to perform the retrospective observational financial analysis, a total of 14 large companies operating on a global scale were identified, and investigated in two distinct groups under pharmaceutical and biotechnology company peer sets. A shareholder value analysis framework was utilized to map out the financial levers of value generation focusing on Total Return on Shareholder Value (TRS) and Return on Invested Capital (ROIC). The relationships between the geographic revenue breakdown and the two aforementioned parameters were tested by conducting a correlation analysis. These two parameters were collected over a three year period from 2009 through 2011. Similarly, a five year period ranging from 2007 through 2011 was also initially explored but then later discontinued since the 2008 economic downturn was identified as a disruptive confounding factor to the ability to draw meaningful conclusions. The correlation analysis was performed separately for pharmaceutical and biotechnology companies. Pharmaceutical companies operate with a more traditional, primary care focused small molecule product portfolio whereas the biotechnology companies discover, develop and market expensive biologics products targeting specialists. Therefore, these two groups of life sciences companies were investigated in separate peer groups. The selected pharmaceutical companies were the largest among their peers by revenue which ranged from $20 to $61 billion. Correspondingly, their market capitalization was also among the highest in their peer set. While these companies were headquartered in the United States, United Kingdom or Switzerland; their common stock were all traded in NYSE. Also, they all recognized revenue through their worldwide operations that would allow to compare performance by geographic denominations. Similarly, seven largest biotechnology companies were all publicly traded in NYSE. Company financials to determine TRS and ROIC were collected through public sources, and later normalized by adjusting their fiscal years to the calendar years to be able to draw comparative conclusions. The qualitative study led to the identification of the following seven key success factors that the pharmaceutical and biotechnology companies need to perform exceptionally well to stay competitive in the Emerging Markets: 1.Local Manufacturing Presence 2.Building Agile Regulatory Affairs Capabilities 3.Commercial Model Addressing Emerging Market Needs 4.Broad and Efficient Distribution Network 5.Dynamic Pricing and Contracting Capabilities 6.Emerging Market Medical Affairs Capabilities Connecting Local Thought Leaders to Global Clinical Development Leaders 7.Access to and Retention of Local Talent The quantitative analysis suggested that TRS did not show a positive correlation with the revenue booked in the Emerging Markets whereas the United States revenue showed a positive correlation. For the same sample set, the ROIC showed a positive correlation with the revenue booked by both pharmaceutical and biotechnology companies, suggesting that in the period of this study life sciences companies that enter the Emerging Markets should not expect an appreciation for their stock price while they will gain some modest returns on their invested capitals.
Keywords: Ekonomi; Finans; İktisat; İlaç; İşletme; Sağlık